Importance of Demand Forecasting within two case companies focusing on production and warehousing - Urosevic, Alex (My University, 2024)
The objective of this research is to explore the importance of demand forecasting within production and warehousing in the coffee industry, with a particular focus on identifying key variables that impact decision making. The main motivation of starting this research came from realizing how volatile and changing our markets are around the globe and how certain factors can trigger a domino effect on the supply chain. With the current supply chain pro-cesses being very volatile and prone to quick changes, it is highly important to see which fac-tors have major impact on processes. This study examines the practices of case company 1 as well as 2, which share the same raw materials but operate in different production locations, however, serve in the same market. Through a qualitative approach and structured inter-views, the research uncovers critical factors such as lead time, communication, as well as con-sumer purchasing trends that influence demand forecasting practices in warehousing as well as production. Key areas include the role of communication with stakeholders, adapting to market changes, as well as understanding the importance of marketing campaigns. The re-search revolves around three main research questions: (1) what role technology play in en-hancing demand forecasting processes in production and warehousing? (2) what are they key factors influencing forecasting accuracy, as well as (3) how does collaboration between stakeholders improve the forecasting accuracy in the coffee supply chain? The study findings show that communication with stakeholders working the supply chain, as well as focusing on understanding campaign, and flexibility are crucial roles in forecasting. understanding these dynamics to optimize inventory management, improve decision making, delivery and sales.
Keywords: forecasts; supply chains; warehousing; demand; logistics; decision making; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management